Caracterización agro socio económica de productores de maíz (Zea Mays), involucrados en el proyecto Fiasa-Iniap, semillas andinas, en las provincias de Pichincha, Cotopaxi y Tungurahua 22-23. - Casaliglla Soria, Denisse Zulay (2023)
This project was developed in Pichincha, Cotopaxi, and Tungurahua provinces belonging to the Ecuadorian Sierra, due to the lack of knowledge regarding the agro-socio-economic conditions, in agreement with the National Institute of Agricultural Research (INIAP) and the Fund Research Center for Agrobiodiversity, Seeds and Sustainable Agriculture (FIASA); therefore, this research has as its primary objective to carry out a characterization to identify the social, economic, and productive situation, for which the Participatory Rural Diagnostic Methodology was used, which consists of collecting information by applying a survey, where the ODK application was used, giving the researcher the data in an SPSS format for subsequent analysis and determine critical points using the modified Sarandón methodology, where values from 0 to 4 were assigned for the global critical issues present in the social,